Suitable Marketing Mix Strategy for Walking Streets in Mae Hong Son - Srika, Wipawee; Chaiyo, Wilaiporn; Kamchai, Kamolthip (วารสารวิชาการนอร์ทเทิร์น, 2024)
This study endeavors to achieve the following objectives, 1. To determine the optimal format for walking street tourist attractions. 2. To scrutinize the prerequisites of tourists’ marketing mix for walking street tourist attractions. 3. To derive guidelines for the advancement of walking street tourist attractions and 4. To utilize the findings of this study as a framework for establishing the paradigm of walking street tourism, thereby fostering sustainable tourism practices. The sample under examination comprises 400 tourists, encompassing both Thai and foreign visitors, currently touring Mae Hong Son. Data collection was conducted through a structured questionnaire. The results indicate that the majority of respondents are females aged 51 years and above, possessing a high school education or its equivalent (such as vocational or high vocational education), engaged in various occupations, and exhibit an average monthly income ranging between 60,001-90,000 Thai Baht. The respondents’ evaluation of the components of the marketing mix for walking streets in Mae Hong Son generally falls within the medium to high range. These components, ranked in descending order of significance, include price, product quality, distribution channels, and promotional activities. When assessing the satisfaction coefficient of tourists towards product development and design on walking streets, according to Kano’s model, emphasis should be placed on products that fulfill tourists’ needs. Kano’s model underscores the following aspects: prioritizing safety in the tourism area, scheduling programs in advance, ensuring the correlation between price and quality of products and services, and highlighting local culture and tradition during local festivals. Additionally, products sold on walking streets should predominantly showcase local craftsmanship. The results of hypothesis testing reveal that age, education, occupation, and average income of tourists do not significantly vary concerning the elements of the marketing mix.